The Influence of Capital Intensity, Inventory Intensity, Leverage, and Profitability on the Effective Tax Rate (ETR) (Empirical Study on Manufacturing Companies in the Food and Beverage Sub Sector Listed on the Indonesia Stock Exchange from 2020-2023) - Arda, Natasya Oktaviani; Rahayu, Sri; Erwati, Misni (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to examine and analyze the effect of capital intensity, inventory intensity, leverage, and profitability on the Effective Tax Rate of food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sampling technique used is purposive sampling, resulting in 29 companies being selected as the research sample. This study is classified as secondary research, where the data was obtained from financial statements (annual reports) available on the official websites of the companies and the Indonesia Stock Exchange (IDX). The analytical method employed is multiple linear regression analysis, processed using IBM SPSS version 25 software (for Windows). The results of the study indicate that the variables of capital intensity and inventory intensity have no significant effect on the Effective Tax Rate, whereas the variables of leverage and profitability have a significant effect on The Effective Tax Rate.